2002
DOI: 10.1055/s-2002-23643
|View full text |Cite
|
Sign up to set email alerts
|

The Possible Involvement of Micro-Organisms Other Than Helicobacter pylori in the Development of Rectal MALT Lymphoma in H. Pylori-Negative Patients

Abstract: It remains unclear whether lymphoma of the mucosa-associated lymphoid tissue (MALT) in the extragastric organs is related to Helicobacter pylori infection or not. This report describes three patients with rectal MALT lymphoma negative for H. pylori infection, all of whom showed disease regression after being treated with antibiotics. One patient had MALT lymphoma in both the descending colon and the rectum; the other two patients had rectal disease only. None of the patients had chronic gastritis which was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 7 publications
3
36
1
1
Order By: Relevance
“…Tumor regression was not affected by the types of antibiotics administered or by the presence or absence of proton pump inhibitors. There were seven reported H. pylori-negative patients, in whom colonic MALT lymphoma regression was attained by the administration of antibiotics; these were the three cases reported by Nakase et al 6 (including one case described by Inoue and Chiba 2 ), the case reported by Oiya and coworkers, 7 and the three cases reported in this study. From these reports, the presence or absence of gastric H. pylori is considered to have had no apparent impact on the effectiveness of antibiotics against colonic MALT lymphomas.…”
Section: Discussionsupporting
confidence: 50%
“…Tumor regression was not affected by the types of antibiotics administered or by the presence or absence of proton pump inhibitors. There were seven reported H. pylori-negative patients, in whom colonic MALT lymphoma regression was attained by the administration of antibiotics; these were the three cases reported by Nakase et al 6 (including one case described by Inoue and Chiba 2 ), the case reported by Oiya and coworkers, 7 and the three cases reported in this study. From these reports, the presence or absence of gastric H. pylori is considered to have had no apparent impact on the effectiveness of antibiotics against colonic MALT lymphomas.…”
Section: Discussionsupporting
confidence: 50%
“…Among several endoscopically observed gross appearances of gastric MALT lymphoma, cobblestone mucosa and a submucosal tumor-like appearance may be clinically relevant for predicting unresponsiveness to antibacterial treatment. In addition, a few cases of MALT lymphoma arising in anatomical sites other than the stomach were documented to show disease regression after being treated with antibiotics, 49,50 suggesting involvement of H. pylori or other microorganisms in its development. This phenomenon should be also comprehensively analyzed to broaden the clinical implication of antibacterial treatment for MALT lymphoma.…”
Section: Resultsmentioning
confidence: 99%
“…We also experienced CR achieved in a patient who did not respond to the standard first-line eradication therapy and therefore received metronidazole (patient 1). In addition, previous studies reported that H. pylori eradication therapy was effective for H. pylori-negative rectal MALT lymphomas (Nakase et al 2002;Nomura et al 2010). These previous reports and our study suggest the possibility that microorganisms other than H. pylori are involved in the development of MALT lymphomas, which could account for the effectiveness of different antibiotics on H. pylori negative MALT lymphomas, but further studies are warranted.…”
Section: Discussionmentioning
confidence: 97%